سرعة الانطلاق وعلاقتها بالإنجاز لدى رماة الرمح السوريين - الشمق, غفران (Latakia University Journal -Medical Sciences Series, 2017)
تأتي أهمية استخدام وسائل التحليل الحركي التي يعتمدها علم الميكانيكا الحيوية في المساعدة على كشف الأخطاء التي ترافق الأداء من خلال تحديد قيم المتغيرات التي تمثل مواصفات الأداء ، أو لتحديد نقاط الضعف ومعالجتها ،أو اضافة وسائل ومعينات أكثر فاعلية لتطوير الأداء وتركز هذه الدراسة على تحديد قيم متغير سرعة انطلاق الرمح وعلاقته بالإنجاز ،وقد طبقت الدراسة على 5 رماة رمح سوريين من أعضاء المنتخب الوطني والذين شاركوا في بطولات عربية وأسيوية. وقد توصلت الدراسة إلى وجود علاقة ارتباط معنوية بين سرعة الانطلاق والانجاز لدى رماة الرمح السوريين وانخفاض مستوى سرعة انطلاق الرمح وتدنى هذا المستوى عن المستوى الذي حققه الأبطال العالميين. ومن أهم التوصيات التي أوصت بها الباحثة إعطاء حيز كبير من الاهتمام لتنمية سرعة الانطلاق وتحسين المتغيرات ذات الارتباط بها وعدم اعتماد التقييم العشوائي في تحديد أسباب التدني أو انخفاض المستوىThe use of kinetic analysis adopted by the biomechanics is significant because it may help to detect the mistakes associated with performance by determining the variables values that represent performance specifications, or to identify and address the weaknesses, or to add more active means and aids to develop the performance. This study focuses on the javelin release speed variable and its relation to the achievement. The study applied on 5 Syrian javelin throwers of national team who participated in Arab and Asian championships.The study concluded that there issignificant correlation between the javelin release speed and the achievement. The study also concluded the low release speed of the javelin compared with international champions.The researcher recommended to give more attention to the development of the javelin release speed and to improve the relevantvariables, and not to adopt the random assessment in determining the reasons of the low level.